Growth of Tree and Yield of Intercrop as Influenced by Tree Densities under Hardwickia binata Based Agrisilviculture System in Semi-arid Conditions of India - ., Ajit; Tiwari, Rajeev; Newaj, Ram; ., Uma (Indian Journal of Agroforestry, 2020)
A field experiment was conducted at National Research Centre for Agroforestry, Jhansi to study the influence of tree densities (800, 400 and 200 trees/ha) on growth of Hardwickia binata (Anjan) and yield of intercrop Brassica campestris (mustard) during 1991-1999. The growth data revealed that higher densities of H. binata (800 and 400 trees/ha) increased the height of trees at a faster pace as compared to lower density (200 trees/ha). On the other hand, dbh (diameter at breast height) increased at a rapid rate in lower density in contrast to higher densities. The growth attributes in H. binata showed seasonal variability. Growth in height was maximum during the summer season while the dbh was highest in winter season. The growth pattern of trees in pure stand (sole tree) and agrisilviculture (tree+crop) system exhibited similar trend. The MAI (mean annual increment) of height was nearly 1 m yr-1 [ 1.03 m yr-1 in agrisilviculture and 1.01 m yr-1 in agroforestry] and the MAI of dbh was nearly 2 cm yr-1 [2.06 cm yr-1 in silviculture and 2.01 cm yr-1 in agroforestry]. During the first four years of experimentation, the reduction of mustard crop (in agroforestry) over sole crop was less than 8per cent in all the three tree densities. In lower density of 200 trees ha-1, the reduction in crop yield was less than 5 per cent upto 5th year and increased to 15 per cent by 6th year. However, the reduction in crop yield by 65% in seventh year suggested intensive management of trees is required if crops are to be taken along with trees.